2016
DOI: 10.19104/jors.2016.114
|View full text |Cite
|
Sign up to set email alerts
|

Management of Head and Neck Arteriovenous Malformations - Team work Counts

Abstract: Purpose: To demonstrate the management protocol in head and neck vascular malformation Methods: This is a retrospective review of 12 patients of arteriovenous malformation managed at a teaching hospital. Medical records were examined for age at first diagnosis, disease course, prior treatments, and age at presentation, management, therapeutic outcomes, impact on quality of life and photograph at time of presentation.Results: Twelve patients with head and neck arteriovenous malformation presented to our centre.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…And now the results with embolic agents like Onyx. Close monitoring of malformations as in the treatment of malignancies is therefore necessary (10). There are several evidences in the literature confirming the efficacy of combined treatment as in our case.…”
Section: Discussionsupporting
confidence: 70%
“…And now the results with embolic agents like Onyx. Close monitoring of malformations as in the treatment of malignancies is therefore necessary (10). There are several evidences in the literature confirming the efficacy of combined treatment as in our case.…”
Section: Discussionsupporting
confidence: 70%
“…As an alternative to minimally invasive techniques, such as SRS and embolization, microsurgical resection can also be proposed [30]. As an example, Panda et al [31] reported 12 patients with head and neck AVMs, with 10 undergoing embolization which was followed by surgery. Complete excision was achieved in 8 cases while partial resection was achieved in 2 cases; 3 patients had complications while being treated (the most common were pain, bleeding, and failure of the reconstruction flap requiring revision surgery) [31].…”
Section: Discussionmentioning
confidence: 99%